THE COMPARISON OF LISTENING ACHIEVEMENT USING MEDIA PODCAST WITH MEDIA AUDIO-VISUAL AT DIFFERENT LISTENING HABIT AT THE STUDENTS OF SMA CATUR SAKTI YEAR ACADEMIC 2012/2013 - Juni Bayu Al-Bana (Premise: Journal of English Education and Applied Linguistics, 2013)
Listening is essential in the language classroom because it provides input for the learner. Without understanding input at the right level, learning cannot begin. Nevertheless, many students at SMA Catur Sakti year academic 2012/2013 who are not interested in listening subject so that their listening achievement goes to low. This research tries to compare between media podcast and audio-visual toward listening achievement at different listening habit. To find out the result of the research, the researcher proposes four hypotheses, they are: (1) there is interaction of listening achievement, learning media, and different listening habit; (2) there is difference of listening achievement using media podcast and media audio-visual; (3) there is difference of listening achievement using media podcast and media audio-visual at good listening habit; and (4) there is difference of listening achievement using media podcast and media audio-visual at bad listening habit. This research is true experimental research with Factorial Design. In analyzing data, the researcher uses the formula of two ways anava. Based on the discussion, the researcher finds that the result of calculation gives the important result. It is found that F cal = 8,5 and F table at significance level 1% is 7,11 and at significance level 5% is 4,01. Therefore, F cal > F table, it means that there is interaction of listening achievement, learning media, and different listening habit. Next, it is found that F cal = 85,65 and  F table at significance level 1% is 7,11 and at significance level 5% is 4,01. It means that F cal > F table, it means that there is difference of listening achievement using media podcast and media audio-visual. Students in experiment class tend to have better score than those in the control class so the researcher concludes that media podcast is better to use than media audio-visual. Afterwards, it is found that F cal = 188,73 and F table at significance level 1% is 7,11 and at significance level 5% is 4,01. It means that F cal > F table, it means there is difference of listening achievement using media podcast and media audio-visual at good listening habit and bad listening habit. Thereby, the researcher concludes that listening habit can also influence the students’ listening achievement. Finally, the researcher suggests the teachers to use media podcast to increase the students’ listening achievement at different listening habit.